Fabrication and characterization of double-layer asymmetric dressing through electrostatic spinning and 3D printing for skin wound repair. (June 2022) - Zhang, Ting; Xu, Hao; Zhang, Yonggang; Zhang, Siruo; Yang, Xia; Wei, Yan; Huang, Di; Lian, Xiaojie
Graphical abstract: Highlights: A bilayer asymmetric dressing was developed to mimic the gradient structure of epidermis and dermis. The dense outer layer with better water repellency was made of PCL/PLA by electrostatic spinning. The porous inner layer with water absorbing capacity was made of SA/PVA adding HACC by 3D printing. The bilayer asymmetric dressing has similar mechanical properties to natural human skin. Abstract: Ideal wound dressings provide optimal microenvironment for the reconstruction of damaged tissue. In this work, we fabricated a bilayer asymmetric dressing to mimic gradient structure of epidermis and dermis of skin by combining electrostatic spinning and 3D printing method with properties including surface hydrophilic and hydrophobic, porosity, mechanical as well as antibacterial properties. The outer layer was prepared by optimized PCL/PLA (PP) via electrostatic spinning to mimick epidermis with water repellency and against bacterial penetration, which has a tensile modulus of 19.69 ± 0.66 MPa. While, the inner layer was 3D printed by optimized sodium alginate/polyvinyl alcohol/chitosan quaternary ammonium salt (SPH). The tensile modulus of SPH with a porosity of 70–90% is 0.82 ± 0.01 MPa, and the water content can be achieved above 85%. The antibacterial efficacy of inner layer was tested against Staphylococcus aureus indicating forming inhibition zone with a diameter of 1.61 ± 0.35 cm. In addition, Cell Counting Kit-8 and Live/Dead assay was used to test the viability of human dermal fibroblasts (HFBS), which showed that PP/SPH with 6% PVA had not significant cytotoxic effects. The double-layer asymmetric dressing meets the requirements of skin mechanical properties and provides an effective repair strategy for clinical skin trauma.